Efektifitas Pelatihan Self Management sebagai Upaya Meningkatkan Self Regulated Learning Siswa Kelas VII MTs Sunan Ampel Pare - Beti Malia Rahma Hidayati (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2018)
This research aims to validate of self-management training as to improve self-regulate learning achievement for students of VII grade in MTs SA Pare. Self regulated learning is to access of schooling result achievement, to self-organizing in learning and managing ability of environment conducive schooling; Afterwards, Self management are a set of principles that accomodated of self-monitoring, self-reward, self-contracting, stimulus control for improving students skills in schooling by training. Model of this research is true experiments. For the population choosed from regularly class VII grades student of program; then for sample choosed by properly sampling that is for the students who have low self regulated learning category. It has explored 18 students divided into control group and experimental group by random. For data analysing technique using two ways ANOVA (Two way ANOVA) by using software SPSS version 20. Based on the analysis results, the class who already given and not given self-management training is significantly different, the average self-regulated learning of students who already trained are higher than students who are not trained